Beginner to Intermediate Introduction to Piano Timbre: NAVIGATING THE KEYS - Ünal Akbulut, Emine Ceylan; Küpana, Mürvet Nevra (Academician Publishing Book DOI Portal, 2023)
Bu kitap, piyano timbresine giriş yapmak isteyen başlangıç ve orta seviye piyanistlere yöneliktir. Eser, piyano tuşlarında gezinmeyi öğretmeyi amaçlamaktadır. Kitap, piyano çalmayı öğrenmek isteyenler için temel bilgileri sunmaktadır. Kitapta, piyano çalmak için gerekli teknikler, nota yazma, ses kaydetme ve çalma teknikleri gibi konular ele alınmaktadır. Ayrıca, kitapta yer alan QR kodları aracılığıyla video ve ses kayıtlarına erişim sağlanabilmektedir. Kitap, müzik alanında uzman olan yazarlar tarafından kaleme alınmıştır ve çeşitli uzman görüşlerine de yer vermektedir. Kitap, piyano öğretmenlerine ve öğrencilere rehberlik etmek amacıyla hazırlanmıştır. This book is aimed at beginner and intermediate level pianists who want to delve into piano timbres. The work aims to teach navigating the piano keys. The book provides basic information for those who want to learn to play the piano. Topics such as necessary techniques for playing the piano, note writing, sound recording, and playing techniques are covered in the book. Additionally, access to video and audio recordings can be obtained through the QR codes included in the book. The book is written by experts in the field of music and includes various expert opinions. It is prepared to guide piano teachers and students.